Pengaruh Budaya Organisasi dan Kepuasan Kerja terhadap Kinerja Karyawan PT X - Ratna Ningsih, Sari; Wangsit Supeno (Akmenika: Jurnal Akuntansi dan Manajemen, 2025)
The main instrument used was a questionnaire, and the data were analyzed using multiple linear regression. This study analyzes the influence of organizational culture and job satisfaction on employee performance at PT Easton Urban Kapital. Using a quantitative survey method with 52 respondents, data were collected through questionnaires and processed using multiple linear regression. And he research sample consisted of 52 respondents selected through purposive sampling The results indicate that organizational culture has a positive and significant effect on employee performance, while job satisfaction alone does not show a significant impact. However, when both variables are considered simultaneously, they significantly improve performance. These findings suggest that a strong organizational culture, supported by job satisfaction, is essential for enhancing productivity and sustaining a healthy work environment.